2016
DOI: 10.3168/jds.2016-11303
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Variations in major mineral contents of Mediterranean buffalo milk and application of Fourier-transform infrared spectroscopy for their prediction

Abstract: The aims of this study were (1) to assess variability in the major mineral components of buffalo milk, (2) to estimate the effect of certain environmental sources of variation on the major minerals during lactation, and (3) to investigate the possibility of using Fourier-transform infrared (FTIR) spectroscopy as an indirect, noninvasive tool for routine prediction of the mineral content of buffalo milk. A total of 173 buffaloes reared in 5 herds were sampled once during the morning milking. Milk samples were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…Prediction of K could depend on milk components that are related to osmotic equilibrium in milk, such as lactose. The MIR-based prediction models for K in milk have been built, though model performance varied from moderate to good among studies (Soyeurt et al, 2009;Stocco et al, 2016;Visentin et al, 2016;Franzoi et al, 2019).…”
Section: Prediction Modelsmentioning
confidence: 99%
“…Prediction of K could depend on milk components that are related to osmotic equilibrium in milk, such as lactose. The MIR-based prediction models for K in milk have been built, though model performance varied from moderate to good among studies (Soyeurt et al, 2009;Stocco et al, 2016;Visentin et al, 2016;Franzoi et al, 2019).…”
Section: Prediction Modelsmentioning
confidence: 99%
“…Few studies have dealt with the genetics of the mineral composition of milk (van Hulzen et al, 2009;Buitenhuis et al, 2015), in particular because of the large number of individual milk samples that would need to be analyzed and the consequent costs. The use of indirect predictions, such as those based on infrared spectroscopy, provides results with variable accuracy (Soyeurt et al, 2009;Stocco et al, 2016;Malacarne et al, 2018) and needs further evaluation. However, in a study to estimate genetic parameters and detect quantitative trait loci for minerals in 456 Danish Holstein and 436 Danish Jersey cows, Buitenhuis et al (2015) showed that the minerals in milk, in particular Ca, P, Mg, and Zn, have high heritability (0.57, 0.62, 0.60, and 0.41, respectively).…”
Section: Detailed Macro-and Micromineral Profile Of Milk: Effects Of mentioning
confidence: 99%
“…In any case, despite the technological advances in analytical methods (Lucey et al, 2017), the use of specific laboratory analysis is almost cost prohibitive for application at the population level, as well as being time consuming. On the other hand, for those minerals predicted with sufficient accuracy (i.e., Na, P, and Ca), Fourier-transform infrared spec-troscopy could be a good compromise between time and cost of analysis, and a useful tool, especially if applied in selective breeding programs in cows (Soyeurt et al, 2009) and in buffaloes (Stocco et al, 2016).…”
Section: Direct and Indirect Effects Of Breedmentioning
confidence: 99%
“…Buffalo milk is a rich source of nutrients and therefore plays an important role in human nutrition, particularly in developing countries (e.g., ~70% of buffalo milk is produced in India; FAOSTAT 2013). Indeed, buffalo milk has higher contents of protein and fat (Ahmad et al, 2013) and minerals (Stocco et al, 2016) than cow milk, whereas some specific classes of gangliosides seem to be only present in buffalo milk (Colarow et al, 2003). The high fat content of buffalo milk makes it also highly suitable for processing (Menard et al, 2010), and in developed countries it is mainly used for the production of a variety of foodstuffs, such as butter, butter oil (ghee), soft and hard cheeses, condensed and evaporated milk, ice cream, yogurt, buttermilk, and in Italy, the highly popular buffalo mozzarella obtained under the European Union's protected designation of origin scheme.…”
Section: Introductionmentioning
confidence: 99%